Case Report: Autoimmune encephalitis and other neurological syndromes with rare neuronal surface antibody in children after hematopoietic stem cell transplantation - Zhang, Ming-min; Wang, Jing; Sun, Dan; Wang, Jing-xuan; Zhang, Jun-hong; Xu, Jia-wei (Frontiers in Immunology, 2023)
Neuronal surface antibody syndromes (NSAS) encompass a growing set of autoimmune neurological disorders, with their predominant clinical presentation being autoimmune encephalitis (AE). The most extensively documented form within NSAS is anti-N-methyl-Daspartate receptor (NMDAR) autoimmunity. In contrast, other NSAS, such as anti-metabotropic glutamate receptor-5 (mGluR5) autoimmunity, are less common and less comprehensively characterized, particularly in pediatric cases.In this instance, we present the case of a 7-year-old girl who exhibited abnormal behavior following hematopoietic stem cell transplantation (HSCT). She received a diagnosis of anti-mGluR5 AE, and her Electroencephalogram (EEG) displayed an increased number of generalized slow waves during wakefulness. Treatment involved intravenous administration of gamma globulin and methylprednisolone, followed by oral prednisone tablets. Levetiracetam was introduced as an antiepileptic therapy during the pulse steroid therapy. Notably, the abnormal behaviors exhibited significant improvement after treatment.To the best of our knowledge, this is the first report of rare pediatric NSAS involving anti-mGluR5 AE following HSCT. Enhancing our understanding and characterization of this condition may facilitate its recognition and treatment in children. Serum antibody testing could enable early identification and treatment of anti-mGluR5 AE.